Examining Individual Earthquake Preparedness Behaviors in Istanbul, Türkiye: A Stage-Based Study Applying the Precaution Adoption Process Model - Ömer Demir; Nuran Aydemir (International Journal of Disaster Risk Science)
Abstract Contemporary disaster risk management emphasizes the importance of mitigation and preparedness. Individual preparedness is essential for mitigating hazard impacts. This study examined earthquake preparedness behaviors through the lens of the precaution adoption process model (PAPM), a health psychology framework. The study aimed to identify differences among individuals at various PAPM stages regarding factors influencing preparedness. The sample consisted of 577 participants, aged 18 to 62, residing in Istanbul. After data collection, group comparison tests were conducted. The findings suggest significant differences between individuals in Stage 3 (undecided about acting) and those in Stage 5 (decided to act) regarding fatalism, perceived barriers, perceived benefits, subjective norms, and perceived behavioral control. Participants who decided to act (Stage 5) reported lower levels of perceived behavioral control than did those who had already acted (Stage 6). Future intervention studies should develop strategies to reduce fatalism and perceived barriers while enhance perceived benefits, subjective norms, and perceived behavioral control to encourage individuals to decide on performing earthquake preparedness behaviors. Increasing perceived behavioral control is essential in future intervention programs to facilitate the transition to action among individuals who have decided to perform preparedness behaviors. More comprehensive mixed-methods studies are needed to thoroughly identify the barriers to preparedness behaviors among individuals at different stages of the PAPM. In addition, more longitudinal studies are necessary to understand the dynamics between stages better.